Investigation of Active Fitness Sportsman Attitudes toward Supplement Intake - Duran, Bülent; Aykora, Emrah (Progress in Nutrition, 2021)
Study Objectives: This study aimed to investigate attitudes of actively doing fitness sportsmen toward nutritional supplements usage and intake. Methods: Quantitative experiment group including 104 [n=36 female, n=68 male] sportsmen while qualitative is 17. Data collected with the “Supplement Belief Scale” developed by Hurst, Foad, Coleman and Beedie (2017) (11) and adapted in Turkish by Karafil, Ulaş and Atay (2019) (12). Quantitative data analysed with independent sample t test and one way ANOVA and qualitative data with content and descriptive analyse method. Results: It is clear from the study that there is a meaningful difference between gender and years of doing sports variables. Male sportsmen more tended to use supplements than females. Also, beginner fitness sportsman are more inclined either. The final evaluation of findings shows both genders have similar attitudes. Conclusion: According to findings because of similar attitudes towards usage of supplements of both genders, in order to reach the most effective results usage preferences come first. It is derived from unconscious intake of supplements by beginners wondering fast body shaping results. Besides one group of participants have a conscious approach and have attitudes for asking expert thoughts about the usage of supplements.